Lithium secondary battery and electric device
Patent Information
- Application Number
- CN202510412341.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2026-10-16
AI Technical Summary
在锂二次电池充放电过程中,负极活性材料尤其是硅基材料体积膨胀收缩,使得表面SEI(Solid Electrolyte Interphase,固体电解质界面膜)不稳定,不断破裂和生长,SEI生长过程中伴随着活性锂的消耗,从而降低可逆锂含量,恶化电池的寿命
[0007] This application includes at least the following beneficial effects: The lithium secondary battery of this application, for batteries in which the silicon-based material content in the negative electrode active material layer is 5%-30%, adds unsaturated sulfides. Unsaturated sulfides are more likely to participate in the formation of a stable SEI on the silicon-containing negative electrode during battery cycling, reducing the continuous cracking and growth of the SEI on the silicon-containing negative electrode, thereby significantly improving the cycle life of the lithium secondary battery.
Smart Images

Figure CN122931015A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of secondary batteries, specifically relating to a lithium secondary battery and an electrical device. Background Technology
[0002] Lithium-ion batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace and many other fields.
[0003] As lithium-ion batteries continue to expand into power and energy storage applications, the demand for long-life batteries is increasing. During the charging and discharging process of lithium-ion batteries, the volume expansion and contraction of the negative electrode active material, especially silicon-based materials, makes the surface SEI (Solid Electrolyte Interphase) unstable, causing it to continuously crack and grow. The growth of the SEI is accompanied by the consumption of active lithium, thereby reducing the reversible lithium content and deteriorating the battery's lifespan. Summary of the Invention
[0004] In view of the technical problems existing in the background art, this application provides a lithium secondary battery, which aims to improve the cycle life of lithium secondary batteries with silicon-containing negative electrodes.
[0005] To achieve the above objectives, the first aspect of this application proposes a lithium secondary battery, which includes a positive electrode, an electrolyte, and a negative electrode. The negative electrode includes a negative active material layer, which includes a silicon-based material. Based on the total mass of the negative active material layer, the mass percentage of the silicon-based material is 5%-30%.
[0006] The electrolyte includes an unsaturated thioester, which comprises a cyclic structure and an unsaturated group attached to the cyclic structure, wherein the cyclic structure comprises one or more of -O-SO2-O-, -O-SO-O-, and -SO2-O-.
[0007] This application includes at least the following beneficial effects: The lithium secondary battery of this application, for batteries in which the silicon-based material content in the negative electrode active material layer is 5%-30%, adds unsaturated sulfides. Unsaturated sulfides are more likely to participate in the formation of a stable SEI on the silicon-containing negative electrode during battery cycling, reducing the continuous cracking and growth of the SEI on the silicon-containing negative electrode, thereby significantly improving the cycle life of the lithium secondary battery.
[0008] In some embodiments, the silicon-based material accounts for 5%-20% of the total mass of the negative electrode active material layer. This can improve the cycle life of the lithium secondary battery.
[0009] In some embodiments, the electrolyte comprises an unsaturated thioester, which includes at least one of the compounds shown in Formula 1, Formula 2, and Formula 3.
[0010]
[0011] In this system, n1, n2, and n3 are each an independent integer from 0 to 2. R1, R2, R3, R4, R5, and R6 each independently include H, halogens, substituted or unsubstituted C1-C10 hydrocarbon groups, aromatic groups, carbonyl groups, carboxyl groups, ester groups, nitrile groups, and isocyanate groups. When substituted, the substituents include halogens. Furthermore, at least one of R1 and R2 includes an unsaturated group, at least one of R3 and R4 includes an unsaturated group, and at least one of R5 and R6 includes an unsaturated group. This improves the cycle life of lithium-ion secondary batteries.
[0012] In some embodiments, R1, R2, R3, R4, R5, and R6 each independently include H, a halogen, or a substituted or unsubstituted C1-C5 saturated or unsaturated alkyl group. When substituted, the substituent includes a halogen, and at least one of R1 and R2 includes an unsaturated group, at least one of R3 and R4 includes an unsaturated group, and at least one of R5 and R6 includes an unsaturated group. This can improve the cycle life of lithium-ion secondary batteries.
[0013] In some embodiments, the unsaturated thioester comprises at least one of the compounds shown in Formula 1 and Formula 2, wherein R1, R2, R3, and R4 each independently comprise H, a halogen, or a substituted or unsubstituted C1-C5 saturated or unsaturated alkyl group, wherein when substituted, the substituent comprises a halogen, and at least one of R1 and R2 comprises an unsaturated group, and at least one of R3 and R4 comprises an unsaturated group. This can improve the cycle life of lithium secondary batteries.
[0014] In some embodiments, the unsaturated thioester comprises at least one of the following compounds:
[0015]
[0016] This can improve the cycle life of lithium secondary batteries.
[0017] In some embodiments, the unsaturated thioester accounts for 0.005%-5% of the total mass of the electrolyte. This can improve the cycle life of the lithium secondary battery.
[0018] In some embodiments, the unsaturated thioester accounts for 0.1%-1.5% of the total mass of the electrolyte. This can improve the cycle life of the lithium secondary battery.
[0019] In some embodiments, the negative electrode sheet includes a negative electrode active material, which includes a silicon-based material; the silicon-based material includes at least one of nano-silicon, micron-silicon, silicon-oxygen materials, and silicon-carbon materials. This can improve the cycle life of lithium-ion batteries.
[0020] In some embodiments, the silicon-based material includes a silicon-carbon material, which comprises porous carbon and nano-silicon disposed within the porous carbon. This can improve the cycle life of lithium-ion batteries.
[0021] In some embodiments, the mass ratio of silicon to carbon in the silicon-carbon material is (4:6) to (6:4). This can improve the cycle life of lithium secondary batteries.
[0022] In some embodiments, the porous carbon comprises mesopores with a pore size of 2 nm to 10 nm and micropores with a pore size of 0.2 nm to 2 nm, wherein the number of mesopores accounts for more than 50% of the total number of pores in the mesoporous carbon. This can improve the cycle life of lithium-ion batteries.
[0023] In some embodiments, the electrolyte further includes fluoroethylene carbonate. This can improve the cycle life of the lithium secondary battery.
[0024] In some embodiments, the fluoroethylene carbonate accounts for 0.5%-20% of the total mass of the electrolyte. This can improve the cycle life of the lithium secondary battery.
[0025] In some embodiments, the fluoroethylene carbonate accounts for 5%-15% of the total mass of the electrolyte. This can improve the cycle life of the lithium secondary battery.
[0026] In some embodiments, the electrolyte further includes other additives, including at least one of saturated or unsaturated cyclic carbonates, sulfite compounds, acid anhydrides, nitrile compounds, aromatic compounds, isocyanate compounds, phosphonitrile compounds, phosphite compounds, phosphate compounds, and borate ester compounds. This can improve the cycle life of the lithium secondary battery.
[0027] In some embodiments, the positive electrode includes a positive active material, which includes Li(Ni) x Co y Mn z O2, where x+y+z=1, and 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2. This can improve the cycle life of lithium secondary batteries.
[0028] In a second aspect of this application, an electrical device is proposed, comprising the lithium secondary battery described in the first aspect of this application.
[0029] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0030] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:
[0031] Figure 1 This is a schematic diagram of a battery according to one embodiment of this application.
[0032] Figure 2 yes Figure 1 An exploded view of a battery according to one embodiment of this application is shown.
[0033] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application.
[0034] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application.
[0035] Figure 5 yes Figure 4 An exploded view of a battery pack according to one embodiment of this application is shown.
[0036] Figure 6 This is a schematic diagram of an electrical device in which a battery is used as a power source according to one embodiment of this application.
[0037] Explanation of reference numerals in the attached figures:
[0038] 1. Battery cell; 11. Housing; 12. Electrode assembly; 13. Cover plate; 2. Battery module; 3. Battery pack; 31. Upper casing; 32. Lower casing. Detailed Implementation
[0039] The embodiments of the technical solution of this application are described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.
[0040] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0041] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0042] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0043] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0044] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0045] Currently, judging from market trends, the application of rechargeable batteries is becoming increasingly widespread. Rechargeable batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, and electric cars, as well as in military equipment and aerospace, among other fields.
[0046] As lithium-ion batteries continue to expand into power and energy storage applications, the demand for long-life batteries is increasing. Silicon-based materials, containing silicon, have a much higher specific capacity than graphite, significantly improving the energy density of lithium-ion batteries and making them a promising anode active material. However, during battery cycling, silicon-based materials undergo severe expansion and contraction, causing instability in the surface SEI (Solid Electrolyte Interphase), leading to continuous cracking and growth. This SEI growth is accompanied by the consumption of active lithium, reducing the reversible lithium content and worsening battery life. Therefore, the content of silicon-based materials in the anode active material layer of the anode electrode should not be excessive.
[0047] For lithium-ion batteries where silicon-based materials account for 5%-30% of the negative electrode active material layer, the stability of the formed SEI can be improved by adding electrolyte additives. Diethyl ester sulfate (DTD) is currently a mature electrolyte additive for improving the lifespan of lithium-ion batteries. Its hypothetical mechanism of action is that during the cycling process of lithium-ion batteries, DTD can generate a sulfate-containing SEI at the negative electrode interface, which has better thermal and chemical stability than carbonates, thereby improving the stability of the negative electrode interface layer itself and reducing the reactivity of the electrolyte at the interface.
[0048] However, in the negative electrode, silicon, being a semiconductor, has poor conductivity, which significantly degrades the ion migration rate. Furthermore, because silicon is a semiconductor, electron transport is hindered in silicon-based materials compared to more conductive carbon-based materials. Considering these characteristics, during the initial charging phase, the additive DTD exhibits significant electrochemical polarization on the silicon-based material, making it difficult for it to participate in the formation of a stable SEI interface component. Therefore, adding DTD to the electrolyte does not significantly improve the lifespan of lithium-ion secondary batteries.
[0049] The lithium secondary battery of this application addresses the issue of silicon-based materials in the negative electrode active material layer. Firstly, by controlling the mass percentage of silicon-based materials in the negative electrode active material layer to 5%-30%, the energy density of the lithium secondary battery is sufficiently increased. Within this silicon-based material content range, the energy density improvement is reduced if the silicon content is too low, while the expansion caused by excessive silicon content is also mitigated. Secondly, to address the problem of silicon-based materials easily expanding during charging and discharging, leading to SEI rupture and recombination, the unsaturated sulfides of this application are added to the electrolyte. Unsaturated sulfides combine sulfur-containing ester groups and branched unsaturated bonds. Introducing these active unsaturated bonds effectively enhances the reactivity of the unsaturated sulfides. Compared to batteries without unsaturated bonds, unsaturated sulfides more readily participate in the formation of a stable SEI during battery cycling. The sulfur-containing ester groups can participate in the formation of sulfates at the interface, improving the chemical stability of the SEI and reducing the probability of SEI rupture caused by the expansion of the negative electrode active material during cycling. In summary, the unsaturated sulfides of this application more readily participate in the formation of a stable SEI during lithium secondary battery cycling, reducing the continuous rupture and growth of the SEI in silicon-containing negative electrodes, thereby significantly improving the cycle life of the lithium secondary battery.
[0050] The lithium secondary battery disclosed in this application can be used in electrical devices that use batteries as a power source or in various energy storage systems that use batteries as energy storage elements. Electrical devices may include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys may include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.
[0051] The first aspect of this application discloses a lithium secondary battery, which includes a positive electrode, an electrolyte, and a negative electrode.
[0052] The negative electrode sheet includes a negative electrode active material layer, which includes a silicon-based material. Based on the total mass of the negative electrode active material layer, the mass percentage of the silicon-based material is 5%-30%.
[0053] The electrolyte includes an unsaturated thioester, which comprises a cyclic structure and an unsaturated group attached to the cyclic structure, wherein the cyclic structure comprises one or more of -O-SO2-O-, -O-SO-O-, and -SO2-O-.
[0054] The lithium secondary battery of this application embodiment, on the one hand, controls the mass ratio of silicon-based material in the negative electrode active material layer to be 5%-30%, which is sufficient to improve the energy density of the lithium secondary battery. Moreover, within the above-mentioned silicon-based material content range, it can reduce the insignificant energy density improvement caused by insufficient silicon-based material content, and can also reduce the excessive expansion caused by excessive silicon-based material content. On the other hand, in view of the problem that silicon-based materials are prone to expansion during charging and discharging, causing SEI rupture and recombination, the unsaturated sulfides of this application embodiment are added to the electrolyte. Unsaturated sulfides are unsaturated bonds that combine sulfur-containing ester groups and branches. Introducing active unsaturated bonds can effectively improve the reactivity of unsaturated sulfides and promote the participation of unsaturated sulfides in the formation of a stable SEI during battery cycling. Sulfur-containing ester groups can participate in the formation of sulfate substances at the interface, improve the chemical stability of SEI, reduce the probability of SEI rupture and recombination caused by the expansion of negative electrode active material during cycling, reduce the increase in battery internal resistance caused by continuous electrolyte consumption, and extend battery life. In summary, the unsaturated sulfides of this application are more likely to participate in the formation of a stable SEI during the cycling process of lithium secondary batteries, reducing the continuous cracking and growth of the SEI in silicon-containing anodes, thereby significantly improving the cycle life of lithium secondary batteries.
[0055] As an example, based on the total mass of the negative electrode active material layer, the mass percentage of silicon-based material can be 5%-29%, 10%-25%, 15%-20%, etc. In other embodiments of this application, the mass percentage of silicon-based material is 5%-20% based on the total mass of the negative electrode active material layer. If the content of silicon-based material in the negative electrode active material layer is too low, the conductivity of the negative electrode sheet is good, but the energy density of the battery is not significantly improved. If the content of silicon-based material in the negative electrode active material layer is too high, the negative electrode active material expands severely during charge and discharge. Adding only the unsaturated sulfide additive of this application is no longer sufficient to achieve the function of stabilizing SEI. Therefore, the content of silicon-based material in the negative electrode active material layer is controlled within the above range.
[0056] It is understandable that the mass ratio of silicon-carbon material based on the total mass of the negative electrode active material layer can be determined by the following methods:
[0057] First, the negative electrode sheet was cut into 6mm×6mm pieces and attached to an ion polishing machine. It was then cut at 7.5kV for 30 minutes, perpendicular to the large surface of the electrode sheet. Following the JY / T010-1996 testing standard, a Sigma300 scanning electron microscope and energy dispersive spectroscopy (EDS) were used for testing and observation. The images showed dark particles as graphite and bright particles as silicon. A single silicon particle was selected to determine the elemental content ratio of silicon and carbon. Then, a large area was selected (the selection area size was defined) for whole-area elemental testing to obtain the ratio of (graphite + carbon) to silicon. Finally, the carbon / silicon elemental ratio of graphite / silicon-carbon was calculated.
[0058] It can be understood that a cyclic structure refers to a compound in which carbon atoms or other atoms (-O-SO2-O-, -O-SO-O-, -SO2-O-) form a closed ring, such as a five-membered ring or a six-membered ring. Silicon-based materials refer to substances containing silicon, such as, but not limited to, elemental silicon, silicon-carbon materials, and silicon-oxygen materials.
[0059] Unsaturated groups are understood to be groups containing unsaturated bonds (such as double and triple bonds) or cyclic structures. These groups have unsaturated carbon atoms and can undergo chemical reactions such as addition reactions with other atoms or groups. Examples include carbon-carbon double bonds (C=C), carbon-carbon triple bonds (C≡C), aromatic groups (such as phenyl), carbon-oxygen double bonds (C=O), carbon-nitrogen double bonds (C=N), and carbon-nitrogen triple bonds (C≡N). A nitrile group refers to -CN, and an isocyanate group refers to -N=C=O, etc.
[0060] In some embodiments of this application, the electrolyte comprises an unsaturated thioester, which includes at least one of the compounds shown in Formula 1, Formula 2, and Formula 3.
[0061]
[0062] Wherein, n1, n2, and n3 are each independently an integer from 0 to 2, and R1, R2, R3, R4, R5, and R6 each independently include H, halogen, substituted or unsubstituted C1-C10 hydrocarbon group, aromatic group, carbonyl group, carboxyl group, ester group, nitrile group, and isocyanate group. When substituted, the substituent includes halogen, and at least one of R1 and R2 in Formula 1 includes an unsaturated group, at least one of R3 and R4 in Formula 2 includes an unsaturated group, and at least one of R5 and R6 in Formula 3 includes an unsaturated group.
[0063] As an example, n1, n2, and n3 can each be 0, 1, 2, etc., independently. When R1, R2, R3, R4, R5, and R6 each independently include substituted or unsubstituted C1-C10 hydrocarbon groups, the number of carbon atoms in the hydrocarbon group can be 1, 3, 5, 7, 9, 10, etc.
[0064] In the embodiments of this application, the unsaturated bonds are located outside the ring of Formulas 1, 2, and 3. Compared with the case of double bonds inside the ring, such as in propenyl sulfonate lactone (PST, structural formula shown below), they are more reactive. Moreover, the unsaturated bonds of PST are located inside the ring, which may affect the reaction process of thioesters, thereby reducing the formation of sulfate substances. In addition, the double bonds located inside the ring will increase the polymerization process, further affecting the viscosity and conductivity of the electrolyte.
[0065]
[0066] It is understandable that unsaturated thioesters in electrolytes can be determined using the following methods:
[0067] In this application, the types and contents of electrolytes are defined in a way known in the art, and can be detected using equipment and methods known in the art. For example, the organic components in the electrolyte can be qualitatively and quantitatively analyzed by gas chromatography using GB / T9722 2006 "General Rules for Gas Chromatography of Chemical Reagents". In this application, freshly prepared electrolyte can be used as a sample, or a fully discharged battery (discharged to the lower limit cutoff voltage so that the battery's state of charge is approximately 0% SOC) can be disassembled in reverse, and the free electrolyte obtained from the battery can be used as a sample for detection using ion chromatography.
[0068] In some embodiments of this application, R1, R2, R3, R4, R5, and R6 each independently include H, halogen, substituted or unsubstituted C1-C5 saturated or unsaturated alkyl groups, wherein when substituted, the substituents include halogens, and at least one of R1 and R2 includes an unsaturated group, at least one of R3 and R4 includes an unsaturated group, and at least one of R5 and R6 includes an unsaturated group. As an example, when R1, R2, R3, R4, R5, and R6 each independently include substituted or unsubstituted C1-C5 saturated or unsaturated alkyl groups, the number of carbon atoms in the alkyl group can be 1, 2, 3, 4, 5, etc. The electron-withdrawing ability of the substituents R1, R2, R3, R4, R5, and R6 is moderate, which makes the unsaturated thioester have high reduction reaction activity in the negative electrode active material layer with a silicon content of 5%-30%, and it is not so active that it participates in the formation of uneven SEI too much or too fast. This makes it easier for the unsaturated thioester to participate in the formation of stable SEI during battery cycling, reducing the continuous cracking and growth of the SEI of the negative electrode, thereby significantly improving the cycle life of lithium secondary batteries.
[0069] In some embodiments of this application, the unsaturated sulfide includes at least one of the compounds shown in Formula 1 and Formula 2, wherein R1, R2, R3, and R4 each independently include H, a halogen, or a substituted or unsubstituted C1-C5 saturated or unsaturated alkyl group, wherein when substituted, the substituent includes a halogen, and at least one of R1 and R2 includes an unsaturated group, and at least one of R3 and R4 includes an unsaturated group. The compounds shown in Formula 1 and Formula 2 make it easier for the unsaturated sulfide to participate in the formation of a stable SEI in the negative electrode active material layer with a silicon content of 5%-30% during battery cycling, reducing the continuous breakage and growth of the SEI in the negative electrode, thereby significantly improving the cycle life of the lithium secondary battery.
[0070] In some embodiments of this application, the unsaturated thioester includes at least one of the following compounds:
[0071]
[0072] Therefore, experiments show that the above-mentioned unsaturated sulfate esters are more likely to decompose in the negative electrode active material layer with a silicon content of 5%-30% during cycling, and generate a stable SEI in the negative electrode. This reduces the SEI cracking and recombination caused by the expansion of the negative electrode active material, and can further improve the cycle life of lithium secondary batteries.
[0073] In some embodiments of this application, the mass percentage of the unsaturated thioester is 0.005%-5% based on the total mass of the electrolyte, for example, it can be 0.005%-4.9%, 0.01%-4.5%, 0.1%-4%, 1%-3.5%, 2%-3%, etc. Controlling the mass percentage of the unsaturated thioester in the electrolyte within the above range can reduce the insufficient amount of unsaturated thioester added, which would lead to insufficient participation in SEI formation and poor effect on improving SEI stability. It can also reduce the excessive consumption of active lithium caused by excessive unsaturated thioester participating in interfacial reactions, which would lead to excessive addition and reduce the deterioration of the first-cycle efficiency of the lithium secondary battery, thereby further improving the cycle life of the battery. In other embodiments of this application, the mass percentage of the unsaturated thioester is 0.1%-1.5% based on the total mass of the electrolyte.
[0074] It is understood that "the mass percentage of unsaturated thioesters based on the total mass of electrolytes" is a well-known definition in the art and can be determined using methods known in the art, such as the following methods:
[0075] Using GC testing
[0076] 1. Sample preparation
[0077] (a) Dilute the electrolyte sample to be tested, usually using deionized water or anhydrous ethanol as the diluent, at a dilution ratio of 1:10 to 1:100 (volume ratio). Avoid introducing impurities during the dilution process to ensure the representativeness of the sample.
[0078] (b) Allow the diluted sample to stand at room temperature for a certain period of time (e.g., 15-30 minutes) to ensure that the sample is fully mixed.
[0079] (c) The sample was filtered using a 0.45 μm filter membrane to remove insoluble particulate matter and obtain a clear test solution.
[0080] 2. Gas Chromatography Instruments and Conditions
[0081] (a) A gas chromatograph (GC) equipped with a flame ionization detector (FID) or a mass spectrometer (MS) is used to achieve efficient separation and quantitative analysis of organic components in the electrolyte.
[0082] (b) Use capillary columns with high resolution, such as DB-1 (non-polar), DB-17 (medium polar) or DB-WAX (polar) columns, with a length of 30-60 meters and an inner diameter of 0.25-0.53 mm.
[0083] (c) The carrier gas is high-purity nitrogen (N2) or helium (He), and the flow rate is 1-5 mL / min.
[0084] (d) The injection method is splitless injection, the injection volume is 0.5-2 μL, and the injection port temperature is 200-250℃.
[0085] (e) The column temperature program is set as follows: the initial temperature is 40-60℃, and the temperature is increased to 200-250℃ at a rate of 5-10℃ / min, and held for 10-30 minutes.
[0086] 3. Preparation of standard solutions
[0087] (a) Prepare a series of standard solutions with concentration gradients, which typically include the main solvent in the electrolyte (such as ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), etc.) and additives (such as unsaturated sulfides, Li salts, flame retardants, etc.).
[0088] (b) The concentration range of the standard solution should cover the concentration range that may exist in the actual sample (e.g., 1-100 mg / mL).
[0089] 4. Sample Analysis
[0090] (a) Inject the prepared test solution into a gas chromatograph for analysis and record the chromatogram.
[0091] (b) By comparing the retention time and peak area of the standard solution, qualitative and quantitative analysis of each component in the sample was performed.
[0092] (c) The concentration or content of each component is determined by calculating the correspondence between the peak area or peak height and the standard curve.
[0093] 5. Data Processing and Result Analysis
[0094] (a) Use gas chromatography data processing software to integrate the chromatographic peaks and calculate the relative peak area or peak height of each component.
[0095] (b) Calculate the concentration of each component in the sample based on the calibration curve of the standard solution, and calculate its mass fraction or volume fraction in the electrolyte.
[0096] (c) Evaluate the performance of the electrolyte (e.g., solvent composition, additive content, etc.) by analyzing the changes in the proportions of each component in the electrolyte.
[0097] 6. Verification of the repeatability and accuracy of test results
[0098] (a) Repeat the test on the sample 3-5 times and calculate the relative standard deviation (RSD) of the peak area of each component to verify the repeatability of the method.
[0099] (b) Compare with known standard substances to verify the accuracy of the method.
[0100] In some embodiments of this application, the electrolyte further includes fluoroethylene carbonate (FEC). As an effective additive, fluoroethylene carbonate can effectively repair the SEI (Sediment Ion) during lithium-ion battery cycling, and the resulting LiF and polymer complex can effectively protect the silicon-based materials. By introducing unsaturated thioesters to enhance their reactivity and participate in the FEC product complex, this product complex is more stable than the layered stacking structure of the products, reducing the continuous cracking and growth of the SEI at the negative electrode, thereby significantly improving the cycle life of the lithium-ion battery.
[0101] In some embodiments of this application, the mass percentage of fluoroethylene carbonate is 0.5%-20% based on the total mass of the electrolyte. For example, the mass percentage of fluoroethylene carbonate can be 0.5%-19%, 1%-17%, 5%-15%, 8%-10%, etc. Controlling the content of fluoroethylene carbonate in the electrolyte within the above range can reduce insufficient SEI repair caused by insufficient FEC addition, reducing the occurrence of cycle failure. It can also reduce the reaction between FEC and lithium salt in the electrolyte to generate acidic substances caused by excessive FEC addition, which would damage the SEI, thus giving the lithium secondary battery excellent cycle life. In other embodiments of this application, the mass percentage of fluoroethylene carbonate is 5%-15% based on the total mass of the electrolyte.
[0102] It is understood that "the mass percentage of fluoroethylene carbonate based on the total mass of electrolytes" is a well-known definition in the art and can be determined using methods well-known in the art, such as GC testing (refer to the mass percentage test of unsaturated thioesters).
[0103] In some embodiments of this application, the silicon-based material includes at least one of nano-silicon, micron-silicon, silicon-oxygen materials, and silicon-carbon materials. Silicon-based materials have a high specific capacity, which is beneficial for the fabrication of high-energy-density batteries. In embodiments of this application, one or more combinations of nano-silicon, micron-silicon, silicon-oxygen materials, and silicon-carbon materials can be used as the silicon-based material, which can effectively improve the energy density of lithium-ion secondary batteries.
[0104] In the negative electrode, the ion migration rate of the solid phase in silicon-based materials is significantly worse than that in carbon-based materials. Furthermore, since silicon is a semiconductor, electron transport is hindered in silicon-based materials compared to the more conductive carbon-based materials. Considering these characteristics, during the first charge stage, the additive DTD exhibits significant electrochemical polarization on the silicon-based material, making it more difficult for it to undergo electrochemical reactions to form a stable SEI interface composition compared to graphite. Therefore, adding DTD to the electrolyte does not significantly improve the lifespan of lithium-ion secondary batteries with silicon-containing negative electrodes. To address the issues of silicon-based materials easily expanding during charge and discharge, leading to SEI rupture and recombination, and the poor conductivity of silicon-containing anodes making it difficult for conventional additives to participate in SEI formation, this application adds an unsaturated sulfide ester to the electrolyte. The unsaturated sulfide ester combines sulfur-containing ester groups and branched unsaturated bonds; introducing active unsaturated bonds effectively enhances the reactivity of the unsaturated sulfide ester, promoting its participation in the formation of a stable SEI. The sulfur-containing ester groups can participate in the formation of sulfate substances at the interface, improving the chemical stability of the SEI and reducing the probability of SEI rupture caused by silicon-based material expansion during cycling. In summary, the unsaturated sulfide ester of this application more readily participates in the formation of a stable SEI during lithium-ion battery cycling, reducing the continuous rupture and growth of the SEI in silicon-containing anodes, thereby further improving the cycle life of silicon-containing lithium-ion batteries.
[0105] In some embodiments of this application, the silicon-based material includes a silicon-carbon material, which comprises porous carbon and nano-silicon disposed within the porous carbon. By placing the nano-silicon within the porous carbon, the nano-silicon can be confined, reducing the expansion of the silicon-based material during lithium-ion battery cycling. This, in turn, reduces the continuous cracking and growth of the SEI in the silicon-containing anode, thereby significantly improving the cycle life of the lithium-ion battery. Furthermore, the carbon acts as an insulator in the electrolyte contact, reducing the contact between acid byproducts and silicon. Moreover, the silicon-carbon material exhibits less expansion and a more stable structure, which, combined with the unsaturated sulfides of the embodiments of this application, further contributes to improving the battery's cycle performance.
[0106] In some embodiments of this application, the mass ratio of silicon to carbon in the silicon-carbon material is (4:6)-(6:4). For example, the mass ratio of silicon to carbon can be (4.1:5.9)-(6:4), (4.5:5.5)-(6:4), (5:5)-(6:4), etc. Controlling the mass ratio of silicon to carbon in the silicon-carbon material within the above range allows the lithium secondary battery containing silicon-carbon material to have excellent energy density, while also reducing the severe expansion of the silicon-containing negative electrode caused by excessive silicon content. Silicon has a poorer ion and electron transport capacity than graphite, resulting in greater interfacial reaction polarization. Unsaturated sulfides can promote interfacial film formation in the above silicon-carbon mixed system, enabling the lithium secondary battery to simultaneously have excellent cycle life.
[0107] It is understood that the mass ratio of silicon to carbon is obtained by calculating the ratio of silicon content to carbon content in a silicon-carbon material. Methods known in the art can be used to determine the silicon and carbon content in silicon-carbon materials. As an example,
[0108] The silicon content test in silicon-carbon materials includes: determining the silicon content using inductively coupled plasma (ICP), specifically as follows: taking silicon-carbon material as a sample, digesting the sample with aqua regia and hydrofluoric acid HF, and taking the completely digested solution for ICP testing.
[0109] Carbon content testing in silicon-carbon materials: carbon-sulfur content analysis by infrared absorption method, tested according to GB / T20123-2006 testing standard.
[0110] In some embodiments of this application, the porous carbon includes mesopores with a pore size of 2nm-10nm and micropores with a pore size of 0.2nm-2nm. The number of mesopores accounts for more than 50% of the total number of pores in the mesoporous carbon. For example, the pore size of the mesopores can be 2nm-9nm, 3nm-8nm, 4nm-7nm, 5nm-6nm, etc., and the pore size of the micropores can be 0.2nm-1.9nm, 0.5nm-1.5nm, 0.8nm-1nm, etc. The number of mesopores accounts for 50%-99%, 60%-90%, 70%-80% of the total number of pores in the mesoporous carbon, etc. By controlling the content of mesopores in the mesoporous carbon within the above range, the number of micropores and mesopores in the porous structure can be controlled to form a porous carbon material with a relatively high specific surface area. This allows for easy control of the silicon content formed within the porous structure, while also reserving some volume space for buffering silicon expansion. By limiting the volume expansion of silicon during lithium insertion / extraction, the cycle performance of lithium secondary batteries can be improved.
[0111] It is understood that "the proportion of mesopores to the total number of pores in mesoporous carbon" is a well-known definition in the art and can be determined using methods known in the art, such as the following methods:
[0112] The distribution of each pore was measured using conventional testing instruments in this field, and the specific quantities were obtained through statistical analysis. For example, an ASAP2460 physical adsorption analyzer was used. The dried and degassed porous carbon material sample was placed in liquid nitrogen, and the amount of nitrogen adsorbed was measured by adjusting different test pressures. Adsorption and desorption isotherms were plotted. The pore shape was determined based on the shape of the hysteresis loop, and the pore distribution was calculated according to different pore models. The BJH model was used to fit the pore size distribution curves of mesopores and macropores, and the DFT model was used to fit the pore size distribution curves of micropores.
[0113] Typically, a battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active metal ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.
[0114] In some embodiments of this application, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector.
[0115] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode active material layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0116] In some embodiments of this application, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0117] In some embodiments of this application, the negative electrode active material may also be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, tin-based materials, and lithium titanate, etc. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0118] In some embodiments of this application, the negative electrode active material layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0119] In some embodiments of this application, the negative electrode active material layer may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0120] In some embodiments of this application, the negative electrode active material layer may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0121] In some embodiments of this application, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0122] In some embodiments of this application, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, wherein the positive active material layer includes the aforementioned irreversible positive electrode additive.
[0123] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive active material layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0124] In some embodiments of this application, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0125] In some embodiments of this application, the positive electrode active material may be a positive electrode active material known in the art for lithium-ion batteries.
[0126] As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.8 Co 0.15 Al 0.05 At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites. The modified compounds of the above materials may be for doping modification and / or surface coating modification of the materials.
[0127] During the charging and discharging process of a battery, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of positive electrode active materials in this application, the molar Li content refers to the initial state of the material, i.e., the state before material addition. After charge-discharge cycles, the molar Li content changes when the positive electrode active material is applied to the battery system.
[0128] In the examples of positive electrode active materials in this application, the molar content of O is only a theoretical value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of O will fluctuate.
[0129] In other embodiments of this application, the lithium transition metal oxide includes Li(Ni) x Co y Mn z O2, where x+y+z=1, and 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2.
[0130] For example, x can be 0.8-0.99, 0.85-0.95, 0.9-0.91, etc.; y can be 0-0.19, 0.05-0.15, 0.1-0.12, etc.; z can be 0-0.19, 0.05-0.15, 0.1-0.12, etc. The lithium transition metal oxides mentioned above have a high nickel content, which can be compatible with silicon-carbon materials for the negative electrode, improving the energy density of lithium secondary batteries while maintaining excellent initial efficiency and cycle life.
[0131] In some embodiments of this application, the positive electrode active material layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0132] In some embodiments of this application, the positive electrode active material layer may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0133] In some embodiments of this application, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder, positive irreversible additive and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0134] This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or completely solid.
[0135] In some embodiments of this application, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0136] In some embodiments of this application, when the battery is a lithium-ion battery, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, or lithium tetrafluorooxalate phosphate. In other embodiments of this application, the lithium salt includes at least one of LiPF6 and LiFSI.
[0137] In some embodiments of this application, the solvent may further include one or more of chain carbonates, cyclic carbonates, carboxylic acid esters, and ethers. The solvent may include at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone, diethyl sulfone, tetrahydrofuran, dimethyl ether, diethyl ether, and ethylene glycol dimethyl ether.
[0138] In some embodiments of this application, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0139] In some embodiments of this application, the electrolyte further includes other additives, including at least one of saturated or unsaturated cyclic carbonates, sulfite compounds, acid anhydrides, nitrile compounds, aromatic compounds, isocyanate compounds, phosphonitrile compounds, phosphite compounds, phosphate compounds, and borate ester compounds. These additives can work in conjunction with the unsaturated sulfides and fluoroethylene carbonates of the embodiments of this application to further improve the cycle life of the lithium secondary battery.
[0140] This application does not impose any particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.
[0141] In some embodiments of this application, the material of the separator may include at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, or polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0142] The secondary batteries of this application include single-cell battery forms, battery module forms, and battery pack forms. The following description, with appropriate reference to the accompanying drawings, will illustrate the single-cell battery, battery module, and battery pack of this application.
[0143] In some embodiments of this application, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly by a winding process or a stacking process.
[0144] In some embodiments of this application, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the aforementioned electrode assembly and electrolyte.
[0145] In some embodiments of this application, the outer packaging of the battery cell can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch-type soft pack. The material of the soft pack can be plastic, and examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0146] It is understood that the lithium secondary battery mentioned above in this application is a single battery cell.
[0147] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 Here is a square-structured battery cell 1 as an example.
[0148] In some embodiments of this application, reference is made to Figure 2 The outer packaging may include a housing 11 and a cover plate 13. The housing 11 may include a bottom plate and side plates connected to the bottom plate, the bottom plate and side plates forming a receiving cavity. The housing 11 has an opening communicating with the receiving cavity, and the cover plate 13 can be placed over the opening to close the receiving cavity. The positive electrode sheet, negative electrode sheet, and separator can be formed into an electrode assembly 12 by a winding process or a stacking process. The electrode assembly 12 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 12. The number of electrode assemblies 12 contained in a single battery cell 1 can be one or more, which can be selected by those skilled in the art according to specific practical needs.
[0149] In some embodiments of this application, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.
[0150] Figure 3 This is battery module 2 as an example. (See reference...) Figure 3 In battery module 2, multiple battery cells 1 can be arranged sequentially along the length of battery module 2. Of course, they can also be arranged in any other way. Furthermore, these multiple battery cells 1 can be fixed in place using fasteners.
[0151] Optionally, the battery module 2 may also include a housing with a receiving space in which multiple battery cells 1 are received.
[0152] In some embodiments of this application, the battery modules described above can also be assembled into a battery pack. The number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0153] Figure 4 and Figure 5This is battery pack 3 as an example. (See reference...) Figure 4 and Figure 5 The battery pack 3 may include a battery box and multiple battery modules 2 disposed within the battery box. The battery box includes an upper box 31 and a lower box 32, with the upper box 31 covering the lower box 32 to form a closed space for accommodating the battery modules 2. The multiple battery modules 2 can be arranged in any manner within the battery box.
[0154] In addition, this application also provides an electrical device, which includes the lithium secondary battery provided in the first aspect of this application. The battery cell, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0155] As the electrical equipment, battery cells, battery modules, or battery packs can be selected according to their usage requirements.
[0156] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.
[0157] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.
[0158] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0159] Experimental Example 1
[0160] 1. Preparation of positive electrode sheet
[0161] An 8μm thick aluminum foil was used as the positive electrode current collector. The positive electrode active material, LiNi, was used. 0.8 Co 0.1 Mn 0.1O2 (NCM811), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are dissolved in solvent N-methylpyrrolidone (NMP) at a weight ratio of 93:2:5. After thorough stirring and mixing, a positive electrode slurry is obtained. The positive electrode slurry is then uniformly coated onto the positive electrode current collector, and after drying, cold pressing, and slitting, a positive electrode sheet is obtained.
[0162] 2. Preparation of negative electrode sheet
[0163] Silicon-carbon material (with a silicon to carbon mass ratio of 5:5, the porous carbon including mesopores with a pore size of 2nm-10nm and micropores with a pore size of 0.2nm-2nm, the number of mesopores accounting for 60% of the total number of pores in the mesoporous carbon), graphite, conductive carbon black, and binder polyacrylic acid are mixed in a mass ratio of 2:6:1:1, and deionized water is added and stirred thoroughly to form a negative electrode slurry; the negative electrode slurry is uniformly coated on one surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.
[0164] 3. Preparation of electrolyte
[0165] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, thoroughly dried lithium salt LiPF6 was dissolved in the mixed organic solvent. Unsaturated thioesters, FEC, PS (1,3-propanesulfonyl lactone), and DTD were added. Based on the total mass of the electrolyte, the mass percentages of unsaturated thioesters were 0.3%, FEC was 10%, PS was 0.7%, and DTD was 0.3%, thus preparing an electrolyte with a lithium salt LiPF6 concentration of 1 mol / L.
[0166] 4. Separating membrane
[0167] A polyethylene film with a thickness of 13 μm was used as the separator.
[0168] 5. Preparation of lithium secondary batteries
[0169] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide insulation. The resulting bare cell is then wound together, tabs are welded onto it, and the cell is placed in an aluminum casing. It is then baked at 80°C to remove moisture, followed by the injection of electrolyte and sealing, resulting in a non-charged battery. This non-charged battery then undergoes a series of processes including settling, hot and cold pressing, formation, shaping, and capacity testing to obtain a lithium-ion battery.
[0170] The preparation method of the lithium-ion battery in Experiment 2-20 is the same as that in Experiment 1, except that the process parameters for preparing the lithium secondary battery are different, as shown in Table 1.
[0171] In Examples 9 and 13, silicon carbide, graphite, conductive carbon black, and polyacrylic acid binder were mixed in a mass ratio of 0.5:7.5:1:1; in Example 10, silicon carbide, graphite, conductive carbon black, and polyacrylic acid binder were mixed in a mass ratio of 1:7:1:1; in Example 11, silicon carbide, graphite, conductive carbon black, and polyacrylic acid binder were mixed in a mass ratio of 3:5:1:1; in Examples 14 and 15, silicon carbide, graphite, conductive carbon black, and polyacrylic acid binder were mixed in a mass ratio of 5:3:1:1; and in Examples 16 and 17, silicon carbide, graphite, conductive carbon black, and polyacrylic acid binder were mixed in a mass ratio of 0.2:7.8:1:1. Compared with Test Example 1, Test Examples 12 and 13, 15 and 16 replaced unsaturated thioester 1-1 with the same amount of DTD; Test Example 19 replaced unsaturated thioester 1-1 with the same amount of vinyl sulfite (ES) compared with Test Example 1; and Test Example 20 replaced unsaturated thioester 1-1 with the same amount of propylene sulfonate lactone (PST) compared with Test Example 1.
[0172] Table 1
[0173]
[0174]
[0175] The internal resistance, cycle life, and storage life of the batteries in Experiment Examples 1-19 were characterized, and the characterization results are shown in Table 2.
[0176] 1. Internal Resistance Test: At 25℃, the shipped lithium-ion batteries and lithium-ion batteries that have undergone 800 cycles at 25℃ are charged to 4.3V at a constant current of 1C. Then, they are charged at a constant voltage of 4.3V until the current is less than 0.05C, and then discharged at 1C for 30 minutes, adjusting the battery capacity to 50% SOC. Then, the positive and negative probes of the TH2523A AC internal resistance tester are connected to the positive and negative terminals of the battery, respectively, and the internal resistance values of the battery are read by the internal resistance tester and recorded as the initial battery internal resistance (mΩ) and the battery internal resistance (mΩ) after 800 cycles.
[0177] 2. Cycle Life Test: At 25℃, the prepared secondary battery (full cell) was charged to 4.25V at 0.5C, and then discharged to 2.5V at 1C. This constitutes one cycle of charge and discharge. The discharge capacity at this point is recorded as the initial discharge capacity. The secondary battery was then subjected to the cycle charge and discharge test as described above, and the discharge capacity after each cycle was recorded until the discharge capacity of the secondary battery decreased to 80% of the initial discharge capacity. The number of cycles at this point was recorded.
[0178] 3. At 25℃, the secondary batteries prepared in each test example were charged at a constant current rate of 0.5C to the charging cutoff voltage of 4.25V, then charged at a constant voltage until the current ≤0.05C, allowed to stand for 5 minutes, and then discharged at a constant current rate of 0.33C to the discharge cutoff voltage of 2V, allowed to stand for 5 minutes. This constitutes one charge-discharge cycle. Then, the batteries were charged at a constant current rate of 0.5C to the charging cutoff voltage of 4.25V, followed by constant voltage charging until the current ≤0.05C. After storing the batteries at 60℃ for 100 days, the batteries were subjected to cyclic charge-discharge tests according to the above method, and the capacity retention rate of the lithium-ion batteries after 100 days of storage was calculated. The results are shown in Table 2.
[0179] Table 2
[0180]
[0181]
[0182] As can be seen from Table 2, in Experiment Examples 1-11, for batteries with a silicon-based material content of 5%-30% in the negative electrode active material layer, the addition of unsaturated sulfides makes it easier for unsaturated sulfides to participate in the formation of a stable SEI on the silicon-containing negative electrode during battery cycling, reducing the continuous cracking and growth of the SEI on the silicon-containing negative electrode, thereby significantly improving the cycle life of lithium secondary batteries.
[0183] Comparing Experiment 12 and Experiment 1, 9-11, it can be seen that when the silicon-based material content in the negative electrode active material layer is 5%-30%, the unsaturated sulfide ester of this application embodiment has a significantly better effect on improving the cycle life of the battery. Comparing Experiment 13 and 14, it can be seen that when the silicon-based material content in the negative electrode active material layer is higher than 30%, the improvement effect of both unsaturated sulfide ester and DTD on the cycle life of the battery is limited. Comparing Experiment 15 and 16, it can be seen that when the silicon-based material content in the negative electrode active material layer is 2%, both unsaturated sulfide ester and DTD have a good effect on improving the cycle life of the battery. It can be seen that conventional DTD can meet the requirement of 2% silicon-based material content in the negative electrode active material layer. However, comparing Experiment 9 and 13, it can be seen that when the silicon-based material content in the negative electrode active material layer is 5%, the improvement effect of unsaturated sulfide ester on the cycle life of the battery is significantly better than that of DTD.
[0184] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A lithium secondary battery, characterized in that, The lithium secondary battery includes a positive electrode, an electrolyte, and a negative electrode. The negative electrode sheet includes a negative electrode active material layer, which includes a silicon-based material. Based on the total mass of the negative electrode active material layer, the mass percentage of the silicon-based material is 5%-30%. The electrolyte includes an unsaturated thioester, which comprises a cyclic structure and an unsaturated group attached to the cyclic structure, wherein the cyclic structure comprises one or more of -O-SO2-O-, -O-SO-O-, and -SO2-O-.
2. The lithium secondary battery according to claim 1, characterized in that, Based on the total mass of the negative electrode active material layer, the mass percentage of the silicon-based material is 5%-20%.
3. The lithium secondary battery according to claim 1 or 2, characterized in that, The unsaturated thioester includes at least one of the compounds shown in Formula 1, Formula 2, and Formula 3: Wherein, n1, n2, and n3 are each independently an integer from 0 to 2, and R1, R2, R3, R4, R5, and R6 each independently include H, halogen, substituted or unsubstituted C1-C10 hydrocarbon group, aromatic group, carbonyl group, carboxyl group, ester group, nitrile group, and isocyanate group. When substituted, the substituent includes halogen, and at least one of R1 and R2 includes an unsaturated group, at least one of R3 and R4 includes an unsaturated group, and at least one of R5 and R6 includes an unsaturated group.
4. The lithium secondary battery according to claim 3, characterized in that, R1, R2, R3, R4, R5, and R6 each independently include H, a halogen, a substituted or unsubstituted C1-C5 saturated or unsaturated alkyl group, wherein when substituted, the substituent includes a halogen, and at least one of R1 and R2 includes an unsaturated group, at least one of R3 and R4 includes an unsaturated group, and at least one of R5 and R6 includes an unsaturated group.
5. The lithium secondary battery according to claim 3 or 4, characterized in that, The unsaturated thioesters include at least one of the compounds shown in Formula 1 and Formula 2, wherein R1, R2, R3, and R4 each independently include H, a halogen, a substituted or unsubstituted C1-C5 saturated or unsaturated alkyl group, wherein when substituted, the substituent includes a halogen, and at least one of R1 and R2 includes an unsaturated group, and at least one of R3 and R4 includes an unsaturated group.
6. The lithium secondary battery according to any one of claims 1-5, characterized in that, The unsaturated thioester includes at least one of the following compounds:
7. The lithium secondary battery according to any one of claims 1-6, characterized in that, Based on the total mass of the electrolyte, the unsaturated thioester accounts for 0.005%-5% of the mass.
8. The lithium secondary battery according to any one of claims 1-7, characterized in that, Based on the total mass of the electrolyte, the unsaturated thioester accounts for 0.1%-1.5% of the total mass.
9. The lithium secondary battery according to any one of claims 1-8, characterized in that, The silicon-based material includes at least one of nano-silicon, micro-silicon, silicon-oxygen materials, and silicon-carbon materials.
10. The lithium secondary battery according to any one of claims 1-9, characterized in that, The silicon-based material includes silicon-carbon material, which includes porous carbon and nano-silicon disposed inside the porous carbon.
11. The lithium secondary battery according to claim 10, characterized in that, In the silicon-carbon material, the mass ratio of silicon to carbon is (4:6)-(6:4).
12. The lithium secondary battery according to claim 10 or 11, characterized in that, The porous carbon includes mesopores with a pore size of 2nm-10nm and micropores with a pore size of 0.2nm-2nm, wherein the number of mesopores accounts for more than 50% of the total number of pores in the mesoporous carbon.
13. The lithium secondary battery according to any one of claims 1-12, characterized in that, The electrolyte also includes fluoroethylene carbonate.
14. The lithium secondary battery according to claim 13, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is 0.5%-20%.
15. The lithium secondary battery according to claim 13 or 14, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is 5%-15%.
16. The lithium secondary battery according to any one of claims 1-15, characterized in that, The electrolyte also includes other additives, which include at least one of saturated or unsaturated cyclic carbonates, sulfite compounds, acid anhydrides, nitrile compounds, aromatic compounds, isocyanate compounds, phosphonitrile compounds, phosphite compounds, phosphate compounds, and borate compounds.
17. The lithium secondary battery according to any one of claims 1-16, characterized in that, The positive electrode sheet includes a positive electrode active material, which includes Li(Ni) x Co y Mn z O2, where x+y+z=1, and 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.
2.
18. An electrical appliance, characterized in that, The lithium secondary battery includes any one of claims 1-17.